A solvent directed D-π-A fluorescent chemodosimeter for selective detection of hazardous hydrazine in real water sample and living cell. (February 2020) - Samanta, Sandip Kumar; Maiti, Kalipada; Ali, Syed Samim; Guria, Uday Narayan; Ghosh, Aritri; Datta, Pallab; Mahapatra, Ajit Kumar
Abstract: Hydrazine being a hazardous environmental pollutant and highly toxic to living organism. Therefore selective, sensitive and rapid detection of hydrazine is much essential for biological and environmental safety. Among various methods for measurement of hydrazine, the fluorescence method based on organic fluorogenic chemosensor is more attractive due to the photo physical characteristics of the fluorophore including high sensitivity. Here, we have synthesized a donor-π- acceptor (D-π-A) based fluorescent molecule (TPB) for rapid and selective detection of hydrazine. Introduction of D-π-A system enhances the ICT character of the probe there by delivered a typical solvatochromism. Accordingly, strong ICT character of the probe is consistent with intense photo physical characteristics to detect hydrazine in different solvent system. Interestingly, the probe showed different optical changes in polar protic and polar aprotic solvent to hydrazine detection. DFT/TDDFT calculation displayed the hypsochromic shift in absorbance and emission spectra were due to disruption of ICT process of the probe upon exposure to hydrazine. In this context, the probe is very much effective for quantitative detection of hydrazine in different real water and soil samples. Also, fluorescence microscopic study revealed that even a trace amount of hydrazine can be detected in living cells by using this probe. Graphical abstract: Image 1 Highlights: A D-π-A system (TPB) facilitates the ICT character of the probe there by delivered a typical solvatochromism. Solvent directed selective ratiometric detection of lethal hydrazine. DFT/TDDFT calculation indicates that hypsochromic shift in absorbance spectra is due to blocking of ICT process. Fluorescence life time studied described that in polar solvent a twisted intramolecular charge transfer was established. The probe TPB is very much effective for quantitative detection of hydrazine in real water, soil samples and in live cell.